Multi-Drug Resistance Mediated by Class 1 Integrons in Aeromonas Isolated from Farmed Freshwater Animals - Deng, Yuting; Wu, Yali; Jiang, Lan; Tan, Aiping; Zhang, Ruiquan; Luo, Li (Frontiers in Microbiology, 2016)
Aeromonas is regarded as an important pathogen of freshwater animals but little is known about the genetics of its antimicrobial resistance in Chinese aquaculture. The aim of this study was to investigate the presence of integrons and characterize multidrug resistant Aeromonas spp. isolated from diseased farmed freshwater animals. These animal samples included fish, ornamental fish, shrimp, turtles and amphibians which were collected from 64 farms in Guangdong province of South China. One hundred and twelve Aeromonas spp. isolates were examined for antimicrobial resistance phenotypes and the presence of class 1 integron sequences. Twenty-two (19.6%) of these isolates carried a class 1 integron comprising 6 different gene insertion cassettes including drfA12-orfF-aadA2, drfA12-orfF, aac(6’)-II-blaOXA-21-cat3, catB3, arr-3 and dfrA17. Among these, drfA12-orfF-aadA2 was the dominant gene cassette array (63.6%, 14/22) and this is the first report of aac(6’)-II-blaOXA-21-cat3 in an A. hydrophila isolate from a Chinese giant salamander (Andrias davidianus). All the integron-positive strains were resistant to more than 5 agents and 22 contained other resistance genes including blaCTX-M-3, blaTEM-1, aac(6’)-Ib-cr and tetA . All integron-positive isolates also contained mutations in the quinolone resistance determining regions (QRDR). Our investigation demonstrates that freshwater animals can serve as a reservoir for pathogenic Aeromonas strains containing multiple drug-resistance integrons. This data suggests that surveillance for antimicrobial resistance of animal origin and a prudent and responsible use of antimicrobials in aquaculture is necessary in these farms.